ANALYZE THE INDUSTRIAL ORGANIZATION SYSTEM, TRANSACTION RELATIONSHIP AND GOVERNANCE MECHANISM FROM THE PERSPECTIVE OF RISK PERCEPTION AND EMOTIONAL BEHAVIOR DRIVING-COMPARATIVE STUDY ON PIG COOPERATIVES IN CHINA - Linlin Fu; Xiaobao Mao; Xiaohong Mao; Jin Wang; Arnon Phuekfhon (My University, 2022)
Abstract Background China is the largest producer and consumer of pigs in the world. It is of strategic significance for China to ensure the stable supply of pigs and improve the production quality of pigs. As a high-risk industry, the pig industry faces six risks: market, capital, disease, policy, environment and transportation. In view of this, the ultimate goal of industry organizations such as cooperatives is to reduce industry risks by reducing transaction costs and establishing governance mechanisms. This study will explore from the perspective of risk perception and action driven Subjects and Methods This paper takes pig cooperatives as the research object. From the perspective of risk perception, based on the analytical framework of “transaction relationship governance mechanism”, this paper divides the transaction relationship of pig farmers into five categories. These five types are: short-term and repeated trading relationship, long-term and stable trading relationship, trading relationship based on written contract, relationship based strategic alliance and equity based strategic alliance. In addition, this paper also defines the corresponding governance mechanisms as market governance, contract governance, relationship governance and equity governance. Based on the analysis framework, through the in-depth analysis and comparison of a large number of cases, this paper mainly analyzes the characteristics of the pig industry organization system, the development and evolution of the transaction relationship of pig farmers and the impact of relevant governance mechanisms. Results It was found that pig cooperatives played an important role in reducing farmers' risk. Specifically, in the upstream relationship, cooperatives reduce farmers' production costs by uniformly purchasing means of production; In the downstream relationship, they increase farmers' income by uniformly selling pigs. In addition, through case comparative analysis, it is found that each transaction relationship has more than one governance mechanism, in which market mechanism is the basis, relationship mechanism is the means, contract mechanism is the guarantee, and equity mechanism is the deepening. In order to better study the changes in risk perception and action, this study used (DASS-21) to conduct a questionnaire survey on the sample. The form was compiled by Ji Jiajun and Lu Jiamei. It has 25 questions and is divided into six dimensions, including emotional perception, emotional evaluation, emotional regulation self-efficacy, effective application of emotional strategies, emotional control and emotional regulation reflection, Presented in the form of self-report of the respondents. For each question, from the six options, please choose one that is in line with your actual situation. From completely inconsistent to fully consistent with the six options, score 1, 2, 3, 4, 5 and 6 respectively. On the six dimensions of this questionnaire α The coefficient is tested to obtain the results of each sub dimension α The coefficients were 0.726, 0.668, 0.831, 0.772, 0.637 and 0.629 respectively α The coefficient is 0.881.cooperatives are important intermediary organizations between the upstream and downstream subjects of agricultural industry. There was a significant positive correlation between the improvement of the index and the ability of emotion regulation (P < 0.01), indicating that the higher the degree of participation, the stronger the ability of emotion regulation. The six dimensions were significantly positively correlated (P < 0.01); At the same time, there was a significant negative correlation between the state of psychological problems and the ability of emotion regulation (P < 0.01). Self control was negatively correlated with emotion perception, emotion evaluation, emotion control and emotion regulation reflection (P < 0.01), negatively correlated with emotion regulation self-efficacy (P < 0.05), and had no correlation with applied emotion strategies. There was a significant positive correlation between emotion regulation ability and all dimensions (P < 0.01); There was a significant positive correlation between encouraging autonomy and emotion regulation ability and each dimension (P < 0.01); There was a significant negative correlation between self-control and emotion regulation ability and each dimension (P < 0.01). Conclusion Since cooperatives are developed by the main body to find a way out, cooperatives have become an effective means of governance and play a vital role in improving farmers' risk awareness, reducing risks and increasing income. Therefore, this study has theoretical and pragmatic significance. Acknowledgments Supported by a project grant from the National Natural Science Foundation of China (Grant No. 71903178).
Keywords: Equity; Asset specificity; Cooperative Studies and Economics